Hysteroscopic management of retained products of conception - Yu-Hui Lin; Yung-Yi Cheng; Dah-Ching Ding (Wolters Kluwer Medknow Publications, 2018)
We report a case with retained products of conception (RPOC) managed by hysteroscopic resection. A 45-year-old woman, G5P3SA1AA1, experienced spontaneous abortion on March 8, 2017, and had persistent vaginal bleeding since then. On May 12, 2017, she came to emergency room where endometrium biopsy was done and revealed degenerative gestational tissue with acute inflammation. On May 23, 2017, she followed up at outpatient department where ultrasonography showed no obvious intrauterine abnormalities with endometrial thickness of 6.5 mm. Office hysteroscopy was arranged and RPOC at the posterior uterine wall was suspected. She received hysteroscopic transcervical resection (TCR) of RPOC on May 26, 2017. After TCR, the vaginal bleeding discontinued. The pathology showed degenerative gestational products with acute inflammation. In conclusion, hysteroscopic TCR might be safe and feasible for RPOC.